The Planning Impact of Boston Nonprofits on Neighborhoods and the Democratic Process. - Anderson, Ina.; Messina, Michael.; Owusu, Emmanuel. (Tufts University. Tisch Library., 2018)
2008 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Community Labor United.